Demographic and Methodological Heterogeneity in Electrocardiogram Signals From Guinea Pigs - Haq, Kazi T.; Cooper, Blake L.; Berk, Fiona; Roberts, Anysja; Swift, Luther M.; Posnack, Nikki Gillum (Frontiers in Physiology, 2022)
Electrocardiograms (ECG) are universally used to measure the electrical activity of the heart; however, variations in recording techniques and/or subject demographics can affect ECG interpretation. In this study, we investigated variables that are likely to influence ECG metric measurements in cardiac research, including recording technique, use of anesthesia, and animal model characteristics. Awake ECG recordings were collected in vivo from adult guinea pigs using a platform ECG system, while recordings in anesthetized animals were performed using both a platform and needle ECG system to record limb lead ECG signals. We report significant heterogeneities in ECG metric values that are attributed to methodological differences (e.g., ECG lead configuration, ECG recording platform, presence or absence of anesthesia) that persist even within the same cohort of animals. Further, we report that variability in animal demographics is preserved in in vivo ECG recordings – with animal age serving as a significant contributor to ECG signal heterogeneity, while sex-specific influences were less pronounced. Methodological approaches and subject demographics should be fully considered when interpreting ECG values in animal models, comparing datasets between studies, or developing artificial intelligence algorithms that utilize an ECG database.